Предмет: Алгебра,
автор: anufrikatya
Помогите, срочно надо!
Приложения:
Ответы
Автор ответа:
7
(2^x)*3^(y + 1) = 72
log(2) (x - y) = 1
(2^x)*3^(y + 1) = 72
x - y = 2
y = x - 2
(2^x)*3^(x - 2 + 1) = 72
(2^x)*3^(x - 1) = 72
(2^x)*(3^x)*(1/3) = 72
(6^x) = 72*3
(6^x) = 216
(6^x) = (6)^3
x = 3
y = 3 - 2 = 1
Ответ: (3;1)
log(2) (x - y) = 1
(2^x)*3^(y + 1) = 72
x - y = 2
y = x - 2
(2^x)*3^(x - 2 + 1) = 72
(2^x)*3^(x - 1) = 72
(2^x)*(3^x)*(1/3) = 72
(6^x) = 72*3
(6^x) = 216
(6^x) = (6)^3
x = 3
y = 3 - 2 = 1
Ответ: (3;1)
Похожие вопросы
Предмет: Русский язык,
автор: Камиль0071
Предмет: Английский язык,
автор: Полинчик2014
Предмет: Английский язык,
автор: Yanaabondaar4311
Предмет: Химия,
автор: fedgizeds